Neuron Deficit in the White Matter and Subplate in Periventricular Leukomalacia - Kinney, Hannah C. (2012)
OBJECTIVE: The cellular basis of cognitive abnormalities in preterm infants with periventricular leukomalacia (PVL) is uncertain. One important possibility is that damage to white matter and subplate neurons which are critical to the formation of the cerebral cortex occurs in conjunction with oligodendrocyte and axonal injury in PVL. We tested the hypothesis that the overall density of neurons in the white matter and subplate region is significantly lower in PVL cases compared to non-PVL controls. METHODS: We used a computer-based method for the determination of the density of MAP2-immunolabeled neurons in the ventricular/subventricular region, periventricular white matter, central white matter, and subplate region in PVL cases and controls. RESULTS: There were five subtypes of subcortical neurons: granular, unipolar, bipolar, inverted pyramidal, and multipolar. The neuronal density of the granular neurons in each of the four regions was 54–80% lower (p≤0.01) in the PVL cases (n=15) compared to controls adjusted for age and postmortem interval (n=10). The overall densities of unipolar, bipolar, multipolar, and inverted pyramidal neurons did not differ significantly between the PVL cases and controls. No granular neurons expressed markers of neuronal and glial immaturity (Tuj1, doublecortin, or NG1). INTERPRETATION: These data suggest that quantitative deficits in susceptible granular neurons occur in the white matter distant from periventricular foci, including the subplate region, in PVL, and may contribute to abnormal cortical formation and cognitive dysfunction in preterm survivors.